Measurement and statistics on science and technology : - Godin, Benoît (Routledge / Taylor & Francis Group, 2005)
A researcher in political science and science policy and statistics, Godin (INRS, Montreal) traces the history of official Western government tracking of statistics and indicators concerning science and technology. Statistical collections started in the 1920s, he says, but only in the 1950s did the first systematic national surveys appear, and were then spread to most countries through the 1963 OECD Frascati manual and to a lesser degree through UNESCO's efforts. He attributes the emergence of such statistics to a dearth of scientists and engineers after World War II, the beginning of science policy, and a new emphasis on the economics of science and technology.